A Literature Review on Conceptual Change: How Does it Contribute to Science Education? - Amiruddin, Mohd Zaidi Bin; Samsudin, Achmad; Suhandi, Andi; Kaniawati, Ida; Aminudin, Adam Hadiana; COŞTU, Bayram; Suliyanah, Suliyanah; Sunarti, Titin; Irfan, Amira Ezzati Binti Mohd; Purwanto, Muhammad Guntur (International Journal of Current Educational Research, 2024)
Objective: Conceptual change is a research trend that continues to develop with various innovations being carried out. The research aims to conduct a literature study on conceptual change and how it contributes to science education. Method: The data was collected by searching for literature sources for articles using specific criteria. Ten articles were synthesized in more depth to answer questions from the research conducted. Result: The results of this research state that methodology and assessment tools influence the form and objectives of research data to be achieved both qualitatively and quantitatively. Apart from that, the concepts in science education are more focused on the physics concepts contained in it. In addition, the findings from these ten articles have a positive impact on science education, especially on material rich in concepts. Novelty: In this way, in making changes to students' conceptions, it is necessary to carry out preliminary studies related to the profile of students and the sample group that you want to research so that it can become a reference for the direction of the research you want to complete.